Ayurvedic Management of Sensory Neural Hearing Loss- A Case Study - Parashar, Akash; Pasha, S M (International Research Journal of Ayurveda & Yoga, 2022)
Introduction: Sensory neural hearing loss occurs when there is damage to tiny hair cells in the cochlear or the auditory nerve. It is characterized by Sudden or steady loss of hearing, Muffled hearing, Difficulty for understanding speech, Ear fullness, Tinnitus and dizziness. According to WHO It is considered the main type of Deafness, which also affects the quality of daily life. In contemporary medicine there is no ideal cure for it, except the application of hearing aid and surgical intervention. In Ayurveda we can correlate it with Badhirya and treat according to it. Thus there is a need to develop an Ayurvedic treatment protocol which is effective and economically viable. Methods: A 34- year old male adult approached OPD of SJIIM Bengaluru, complaining of decreased hearing in both the ears along with tinnitus since 1and a half months. He was taken in for treatment after assessment. Result: After 4 months of treatment, Subjective parameters improved. Conclusion: By the above case study we can conclude that Ayurveda will have a pivotal role in treating cases of Sensory neural hearing loss and in return improving the quality of life.